Gambaran Kasus Nyeri Bahu pada Pasien di Instalasi Rehabilitasi Medik RSUP Prof. Dr. R. D. Kandou Manado Periode Tahun 2020-2022 - Geraldine, Petria F.; Lampah, Christopher; Gessal, Joudy (e-CliniC, 2025)
Abstract: Shoulder pain is one of the leading causes of health problems with a high incidence rate increaseing with age. This condition is the third most common musculoskeletal problem encountered in primary health care visits. This study aimed to obtain the description of shoulder pain cases in patients at the Medical Rehabilitation Installation of Prof. Dr. R. D. Kandou Hospital Manado from 2020 to 2022. This was a descriptive and retrospective study with a cross-sectional design. The results obtained a population of 240 patients; 223 of them met the inclusion and exclusion criteria. Patients who came with complaints of shoulder pain in this study were dominated by patients diagnosed with frozen shoulder (43.9%), the age group of the late elderly (56–65 years) (28.3%), female gender (54.7%), had a work background as housewives (26.5%), had a previous history of hypertension (39%), and had a non-traumatic etiology of the problem (51.2%). In conclusion, patients who presented with shoulder pain were diagnosed with frozen shoulder, aged in the late old elderly, female gender, worked as housewives, had a history of hypertension, and had a nontraumatic etiology. Keywords: shoulder pain; patient characteristics; non-traumatic etiology Abstrak: Nyeri bahu merupakan salah satu penyebab utama gangguan kesehatan dengan tingkat kejadian yang tinggi seiring pertambahan usia dan menempati masalah muskuloskletal ketiga paling sering dijumpai dalam kunjungan ke layanan kesehatan primer. Penelitian ini bertujuan untuk mengetahui gambaran nyeri bahu pada pasien di Instalasi Rehabilitasi Medik di RSUP Prof. Dr. R. D. Kandou Manado periode tahun 2020-2022. Jenis penelitian ialah deskriptif retrospektif dengan rancangan potong lintang. Hasil penelitian mendapatkan populasi sebanyak 240 pasien dengan nyeri bahu; 223 di antaranya memenuhi kriteria inklusi dan ekslusi. Pasien yang datang dengan keluhan nyeri bahu pada peneltitian ini didominasi oleh pasien yang terdiagnosis frozen shoulder (43,9%), kelompok usia masa lansia akhir (56–65 tahun) (28,3%), berjenis kelamin perempuan (54,7%), pekerjaan sebagai ibu rumah tangga (26,5%), memiliki riwayat hipertensi sebelumnya (39%), dan memiliki etiologi permasalahan secara non traumatik (51,2%). Simpulan penelitian ini ialah pasien dengan nyeri bahu terbanyak dengan diagnosis frozen shoulder, berusia masa lansia akhir, berjenis kelamin perempuan, pekerjaan sebagai ibu rumah tangga, mempunyai riwayat hipertensi, serta beretiologi non traumatik. Kata kunci: nyeri bahu; karakteristik pasien, etiologi nontraumatik